2019
DOI: 10.3389/fphar.2018.01558
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: DEAD-Box Helicase 5 Interacts With Transcription Factor 12 and Promotes the Progression of Osteosarcoma by Stimulating Cell Cycle Progression

Abstract: Osteosarcoma (OS) is a common malignant primary bone tumor. Its mechanism of development and progression is poorly understood. Currently, there is no effective therapeutic regimens available for the treatment of OS. DEAD-box helicase 5 (DDX5) is involved in oncogenic processes. This study aimed to explore the role of DDX5 in the development and progression of OS and its relationship with transcription factor 12 (TCF12), which is as an important molecule of Wnt signaling pathway. We found that the expressions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
(65 reference statements)
1
9
0
Order By: Relevance
“…Here, we found that the disruption of antibacterial response caused by Dhx15 depletion in IECs is attributable to a previously unanticipated role of Dhx15 in modulating Wnt/β-catenin signaling. The importance of Wnt/β-catenin signaling in a variety of human diseases is well known, and previous studies have also shown other RNA helicases (DDX3 and DDX5) can regulate Wnt/β-catenin signaling in cell-based experiments (39)(40)(41)(42). Our work confirms that another RNA helicase, Dhx15, affects Wnt/ β-catenin signaling in vivo.…”
Section: Discussionsupporting
confidence: 86%
“…Here, we found that the disruption of antibacterial response caused by Dhx15 depletion in IECs is attributable to a previously unanticipated role of Dhx15 in modulating Wnt/β-catenin signaling. The importance of Wnt/β-catenin signaling in a variety of human diseases is well known, and previous studies have also shown other RNA helicases (DDX3 and DDX5) can regulate Wnt/β-catenin signaling in cell-based experiments (39)(40)(41)(42). Our work confirms that another RNA helicase, Dhx15, affects Wnt/ β-catenin signaling in vivo.…”
Section: Discussionsupporting
confidence: 86%
“…DDX5 has been found to be involved in the oncogenic processes of osteosarcoma. Chen et al [27] proved that the expressions of DDX5 are significantly higher in osteosarcoma patients tissues and osteosarcoma cells. Overexpression of DDX5 is associated with clinicopathological features and poor prognosis of osteosarcoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…DDX5 is a coactivator of transcription factor Fra-1 and DDX5 expression increases Fra-1 transcriptional activity and stimulates cell proliferation in triple-negative breast cancer cells . DDX5 interacts with transcription factor 12 and enhances proliferation of osteosarcoma cells . DDX17, a paralog of DDX5, controls the transcriptional activity of the repressor element 1-silencing transcription factor (REST) in neuronal differentiation .…”
Section: Discussionmentioning
confidence: 99%